Focus, Context, and 'Many' Elements - Tanaka, Takuro (Proceedings of Sinn und Bedeutung, 2019)
This paper investigates the interpretation of the determiner many. Previous literature has pointed out that the interpretation of many requires contextual information. Following this idea, some truth conditions for sentences with determiner many have been suggested. I will show that the analyses proposed in the previous literature are not sufficient, with some data which these analyses cannot explain. This paper argues that the determiner many is focus sensitive, taking a context variable C as its first argument. This context variable provides a set of alternatives for comparison, and predicts a previously unnoticed “list” reading. I will provide a detailed analysis following this idea to explain problematic data for previous analyses, and compare my analysis to the others.